2017
DOI: 10.1007/s40487-017-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

The Readability of Online Patient Resources for Skin Cancer Treatment

Abstract: Introduction: Treatment options for skin cancer vary and to help facilitate the decision-making process many patients will look to online resources. However, general literacy levels in the population are low, making many of these online sources unreadable, worsening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It is our duty as service providers to ensure that the information we provide to patients regarding surgical options is tailored, comprehensive and accessible to patients of all backgrounds and that inequalities in access to surgery are acknowledged, addressed and where possible, surmounted. Our previous work has shown that patient information sheets may not tailor to the average UK reader (44), with 1 in 6 individuals in the UK believed to have a literacy level below that expected of an 11 year old (46), and as a result of this, we are currently working on a bespoke patient information sheet for Microtia to accommodate the variation in literacy skills.…”
Section: Discussionmentioning
confidence: 99%
“…It is our duty as service providers to ensure that the information we provide to patients regarding surgical options is tailored, comprehensive and accessible to patients of all backgrounds and that inequalities in access to surgery are acknowledged, addressed and where possible, surmounted. Our previous work has shown that patient information sheets may not tailor to the average UK reader (44), with 1 in 6 individuals in the UK believed to have a literacy level below that expected of an 11 year old (46), and as a result of this, we are currently working on a bespoke patient information sheet for Microtia to accommodate the variation in literacy skills.…”
Section: Discussionmentioning
confidence: 99%
“…However, because no formula is 100% accurate, the use of more than 1 readability formula when evaluating written content is preferable to improve the validity of the results. 15 Evaluation of online sources of cancer-related information (eg, screening, treatment) [16][17][18][19] has found that information is written at reading levels above the sixth-or seventh-grade level and thus beyond the ability of the average reader. An assessment of 165 988 trials registered as ClinicalTrials.gov 20 through 2014 reported that, on average, 18 years of education (Master's level) are needed to properly understand the trial descriptions using 4 independent readability algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…We used the readability formulae: Flesch-Kincaid Grade Index,24 Coleman-Liau Index,25 Simplified Measure of Gobbledygook Index,26 Gunning-Fog Index27 and the Automated Readability Index 28. We chose these readability formulae as they have previously been used to assess readability within the medical field 15 16 23 29–31…”
Section: Methodsmentioning
confidence: 99%